1987
DOI: 10.1002/hep.1840070315
|View full text |Cite
|
Sign up to set email alerts
|

Increased prolyl hydroxylase activity and collagen synthesis in hepatocyte cultures exposed to superoxide

Abstract: Primary monolayer cultures of rat hepatocytes at confluence were exposed to an exogenously added source of superoxide, and its influence on collagen synthesis was examined. Superoxide was generated by the addition of dihydroxyfumarate to the culture medium. Exposure of hepatocytes to dihydroxyfumarate greatly stimulated the activity of prolyl hydroxylase and the synthesis of collagen. A significant increase in prolyl hydroxylase activity was observed with 5 micrograms per ml dihydroxyfumarate in 24 hr relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Superoxide is known to stimulate collagen synthesis by hepatocytes and fibroblasts in vitro (9,17), and a prooxidant system also induces collagen gene expression and protein production in liver fat-storing cells (35). In addition, oxidative stress, as evidenced by increases in TBARS, stimulates collagen synthesis in the rat aorta in vivo (41).…”
Section: Discussionmentioning
confidence: 97%
“…Superoxide is known to stimulate collagen synthesis by hepatocytes and fibroblasts in vitro (9,17), and a prooxidant system also induces collagen gene expression and protein production in liver fat-storing cells (35). In addition, oxidative stress, as evidenced by increases in TBARS, stimulates collagen synthesis in the rat aorta in vivo (41).…”
Section: Discussionmentioning
confidence: 97%
“…Several isoforms of this enzyme are known to increase in lung and other tissues during various forms of oxidative stress (e.g., 48,70,77), whereas the expression of prolyl hydroxylase-2 increases during chronic hypoxia, leading to a rapid destabilization of HIF-1␣ on reoxygenation (24). Additionally, prolyl hydroxylase activity is inhibited dosedependently by nitric oxide (NO) donation under normoxic conditions leading to HIF-1␣ accumulation in the absence of hypoxia (65,83).…”
Section: Hypoxia-inducible Factor-1␣ (Hif-1␣) and Nuclear Factor-b (Nmentioning
confidence: 99%
“…Both lysyl and prolyl hydroxylases were reported to be inhibited by several low molecular weight copper chelates with SOD-like activity [165]. Additional studies showed that paraquat, a good radical generator, enhanced collagen synthesis in cultured rat lungs [166]; direct generation of superoxide had a similar effect on hepatocytes [167]. On the other hand, culture of rat tibias in the presence of H 2 O 2 decreased collagen production dramatically [168].…”
Section: Collagenmentioning
confidence: 95%